Arctic Environmental Test of Tactical Wire Communications Equipment - ARMY TEST AND EVALUATION COMMAND ABERDEEN PROVING GROUND MD (1970)
The Environmental Test Procedure describes test methods and techniques for evaluating the performance and characteristics of tactical wire communications equipment under arctic winter conditions. The evaluation is related to criteria expressed in applicable Qualitative Materiel Requirements (QMR), Small Development Requirements (SDR), or other appropriate design requirements and specifications. (Author)